A Cu Nanoparticles‐Assisted‐Catalysis Method Enables Controllably Direct Growth of Graphene Transparent Conductive Films on SiO2 Nanospheres Antireflection Layer. Issue 19 (14th June 2022) - Yin, Wanying; Huang, Yue; Lu, Meng; Li, Dezeng
Abstract: The regulation of catalyst distribution is crucial to enhance transmittance of graphene transparent conductive films (TCFs) maintaining their high electrical properties in the chemical vapor deposition (CVD) process. We successfully regulated the distribution of Cu nanoparticles (NPs) and realized the controllable deposition of graphene on the insulating substrates coated with SiO2 nanospheres antireflection (SiO2 NSs AR). The graphene/SiO2 NSs AR composite TCFs prepared with optimized conditions have transmittance of 95.86 % and sheet resistance of 0.934 kΩ ⋅ sq −1 . Compared with graphene TCFs with a whole coated distribution of Cu NPs, the optical properties of graphene/SiO2 NSs AR composite TCFs were significantly improved. Meanwhile, it can maintain a comparable or even lower sheet resistance. This method is easier‐operational, low‐cost and lays a foundation for preparing high‐quality graphene TCFs for future electronic devices. Abstract : Graphene was directly and controllably deposited on the SiO2 nanospheres antireflection (AR) layer via a Cu nanoparticles assisted‐catalysis atmospheric pressure CVD process. The comparison has been made showing that the graphene composite TCFs in this paper (S‐GE/AR) possess better optical properties ensuring comparable electrical properties simultaneously.